Incidence of Coagulase Negative Staphylococci in Various Clinical Samples in Tertiary Care Hospital, Nepal - Shah, Pradeep Kumar; Bhandari, Niru; Joshi, Rajendra D. (Tribhuvan University Journal of Microbiology, 2023)
Objectives: To determine incidence of coagulase negative Staphylococci (CoNS) in various clinical samples along with the study of their multi drug resistance, methicillin resistance and biofilm formation. Methods: A hospital based cross-sectional study was conducted which included 1875 clinical samples. The isolation and identification of isolates was done following standard microbiological protocol. The CoNS were identified phenotypically on the basis of gram staining, slide and tube coagulase test and through various carbohydrates fermentation tests. Antibiotic susceptibility test was done by Kirby Bauer disk diffusion method (Clinical and Laboratory Standards Institute 2020) whereas biofilm production was determined by Tissue Culture Plate (TCP) technique. Results: A total of 32 CoNS, comprising of 6 species were identified. S. epidermidis (43.8%) was the most common species isolated followed by S. saprophyticus (28.1%), S. haemolyticus (15.6%), S. hominis (6.3%), S. lugdunensis (3.1%) and S. cohini (3.1%). Further, 27 (84.4%) of CoNS were found to be multidrug resistant, 22 (68.8%) methicillin resistant and 8 (25%) showed positive D- test. Strong biofilm production was detected in 9 (28.1%) isolates of CoNS, 10 (31.3%) were moderate biofilm producers and 13 (40.6%) non/weak biofilm producers. The equal distribution, 9 (33.3%) each of strong, moderate and non/weak biofilm producers were found among 27 isolates of MDR. Among 22 methicillin resistant isolates, 9 (40.9%), 7 (31.8%) and 6 (27.3%) were strong, moderate and non/ weak biofilm producers respectively. All isolates were sensitive against Linezolid followed by Cotrimoxazole. Conclusion: The increasing multi drug resistance among CoNS should be rationally approached with the use of proper antibiotics while treating the patients.